Sistem Pendukung Keputusan Pemilihan Baju Tunik Wanita Berbadan Gemuk Menggunakan Metode AHP: Sistem Pendukung Keputusan Pemilihan Baju Tunik Wanita Berbadan Gemuk Menggunakan Metode AHP - Dewi Yohana Br Ginting; Putri Karolina; Melvarina Tamba (STMIK Budi Darma, 2021)
Basically the dedecision is a systematic approach to the nature of a problem, gathering facts, determining which mature than the alternative, and taking action according to the calculation is the most appropriate action. Descision makers are often faced with the complexity and scope of decision-making with so much data. For the sake of it, a large part part of the decision-makers to consider the risk benefits or costs, faced with the necessity to realy on a set o systems that sare able to solve the problem efficiently and effectivel, which was then called the Decision Support System(DSS). The working principle of AHP is a simplification of a complex problem that is not structured, strategic and dynamic into its parts, and arrage in a hierarchy. Then the level of importance of each variable given a numerical value subjectively about the importance of these variables in relative terms compared to other variables. From these considerations then do the synthesis to define a variable that has high priority and serves to affect the outcomeof the system. Expert Choiceisa software that can help decision-makers examine and resolve problems involving several evaluation criteria. The software uses a methodology Analytical Hierarchy Process(AHP) for modeling decision problem and evaluate alternative desire. Functional Hierarchy with the overall goal area at thehighest level. The lower levels in accordance with the criteria and sub-criteria each used to choose among alternatives.